Corticotrigeminal Projections from the Insular Cortex to the Trigeminal Caudal Subnucleus Regulate Orofacial Pain after Nerve Injury via Extracellular Signal-Regulated Kinase Activation in Insular Cortex Neurons - Wang, Jian; Li, Zhi-Hua; Feng, Ban; Zhang, Ting; Zhang, Han; Li, Hui; Chen, Tao; Cui, Jing; Zang, Wei-Dong; Li, Yun-Qing (Frontiers in Cellular Neuroscience, 2015)
Cortical neuroplasticity alterations are implicated in the pathophysiology of chronic orofacial pain. However, the relationship between critical cortex excitability and orofacial pain maintenance has not been fully elucidated. We recently demonstrated a top-down corticospinal descending pain modulation pathway from the anterior cingulate cortex (ACC) to the spinal dorsal horn that could directly regulate nociceptive transmission. Thus, we aimed to investigate possible corticotrigeminal connections that directly influence orofacial nociception in rats. Infraorbital nerve chronic constriction injury (IoN-CCI) induced significant orofacial nociceptive behaviors as well as pain-related negative emotions such as anxiety/depression in rats. By combining retrograde and anterograde tract tracing, we found powerful evidence that the trigeminal caudal subnucleus (Vc), especially the superficial laminae (I/II), received direct descending projections from granular and dysgranular parts of the insular cortex (IC). Extracellular signal-regulated kinase (ERK), an important signaling molecule involved in neuroplasticity, was significantly activated in the IC following IoN-CCI. Moreover, in IC slices from IoN-CCI rats, U0126, an inhibitor of ERK activation, decreased both the amplitude and the frequency of spontaneous excitatory postsynaptic currents (sEPSCs) and reduced the paired-pulse ratio (PPR) of Vc-projecting neurons. Additionally, U0126 also reduced the number of action potentials in the Vc-projecting neurons. Finally, intra-IC infusion of U0126 obviously decreased Fos expression in the Vc, accompanied by the alleviation of both nociceptive behavior and negative emotions. Thus, the corticotrigeminal descending pathway from the IC to the Vc could directly regulate orofacial pain, and ERK deactivation in the IC could effectively alleviate neuropathic pain as well as pain-related negative emotions in IoN-CCI rats, probably through this top-down pathway. These findings may help researchers and clinicians to better understand the underlying modulation mechanisms of orofacial neuropathic pain and indicate a novel mechanism of ERK inhibitor-induced analgesia.